(untitled) (Fenestella. Inside Medieval Art, 2020)
Santa Maria of Taüll : The Eucharistic and Angelic Painted Programme of the South Aisle The paintings on the south aisle of Santa Maria of Taüll located in the second bay, just after the bell tower, concentrate several themes related to the Eucharist : the appearing of Gabriel to Zechariah, the Divine Lamb, a nimbed figure dressed in liturgical garments and two fish flanking a cross. The first theme is particularly significant since it includes two clues that clarify the thinking of the designer : a chalice stands on the altar and it is the archangel who holds the censer and not the father of John the Baptist. As in several other Catalan churches, it is therefore the censing of the Oblates that refers to the sacrifice of the Mass. We can therefore assume that an altar was erected near these images and that it was dedicated to the angels, because the paintings above the appearing of Gabriel represent warrior angels and that this scene is adjacent to the bell tower. As in many elevated places of worship dedicated to Saint Michael or to the angels, two themes have therefore been connected with these winged beings. There are consequently high probabilities that the singular iconographic program of Taüll was intended to accompany the cult of the angels celebrated in the nave, in the tower or in both places.